Correlation between Demographic Characteristic and Oxidized Low Density Lipoprotein (OxLDL-IgM and OxLDL-IgG) Antibodies levels in patients with Systemic Lupus Erythematosus Patients - Al-Zubaidi, Nusaibah K.; Al-Fakhar , Suha A.; Al-Osami, Mohammad H. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Systemic Lupus Erythematosus (SLE) may affect one or more organ systems; as time goes on, other manifestations may appear. Musculoskeletal, cutaneous, renal, and endocrine systems are all involved in SLE. The nervous system, hematological, vascular, pulmonary, gastrointestinal, and ocular imbalance of the immune response and the production of autoantibodies such as anti-oxidized Low-Density Lipoprotein LDL antibodies have a clear impact on the body’s organs and the development of complications of the disease. Objectives: To assess the levels of anti-oxLDL (IgM-Abs) and anti-oxLDL (IgG-Abs) as biomarkers for disease activity in SLE patients and their relationship to demographic characteristics. Methods: The study comprised 100 SLE patients admitted to the Rheumatology Unit at Baghdad Teaching Hospital, age range (33.4 to 9.95) years, including 7 males and 93 females. An enzyme-linked immunosorbent Assay ELISA was used to measure the levels of serum oxLDL (IgM- Abs) and oxLDL (IgG-Abs). Results: The results of the present study showed that there was a significant difference between the levels of anti-oxLDL IgM antibodies(Abs) in SLE patients in obese and non-obese groups since the levels of anti-oxLDL-IgM Abs in obese patients were (3.14 µg/L) and non-obese patients were (5.13 µg/L) (P=0.005), while in SLE patients with Diabetes Mellitus (D.M.), the levels of anti-ox LDL-IgM Abs were (3.80 µg/L) and in SLE patients with no DM were (5.13 µg/L). Also, the results showed that there were no significant differences between levels of anti-oxLDLIgG Abs in obese patients with SLE (6.28 µg/L) and non-obese patients with SLE (10.25µg/L) P > 0.05. Conclusion: There was a significant difference between levels of anti-oxLDLIgM Abs in obese and non-obese patients with SLE, and no significant differences between the levels of anti-oxLDL IgG Abs in the same groups of patients.